2020
DOI: 10.1556/2006.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Framework of Harmful Gambling: A revised framework for understanding gambling harm

Abstract: Background and aims The Conceptual Framework of Harmful Gambling moves beyond a symptoms-based view of harm and addresses a broad set of factors related to the risks and effects of gambling harmfully at the individual, family, and community levels. Coauthored by international research experts and informed by multiple stakeholders, Gambling Research Exchange (GREO) facilitated the framework development in 2013 and retains responsibility for regular updates and mobilization. This review article pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 113 publications
(113 reference statements)
1
27
0
Order By: Relevance
“…Gambling-related behaviors are not only explained by environmental factors, but also by the interaction of these with individual factors (Blaszczynski & Nower, 2002;Hilbrecht et al, 2020). Our findings make a contribution in this regard and are in line with Banduras's (1977Banduras's ( , 1986 self-efficacy theory, suggesting that even in the presence of environmental cues that encourage gambling, abstinence from gambling is highly dependent on personal efficacy expectations of gambling avoidance.…”
Section: Discussionsupporting
confidence: 86%
“…Gambling-related behaviors are not only explained by environmental factors, but also by the interaction of these with individual factors (Blaszczynski & Nower, 2002;Hilbrecht et al, 2020). Our findings make a contribution in this regard and are in line with Banduras's (1977Banduras's ( , 1986 self-efficacy theory, suggesting that even in the presence of environmental cues that encourage gambling, abstinence from gambling is highly dependent on personal efficacy expectations of gambling avoidance.…”
Section: Discussionsupporting
confidence: 86%
“…In that era gambling studies also encompassed anthropological and archaeological studies more generally (e.g., Gabriel, 1996). More recent research on Indigenous gambling is situated within a harm reduction approach (Hilbrecht et al, 2020) or problem gambling approach (Williams et al, 2021;Saunders & Doyle, 2021). Within a critical Indigenous studies framework, then, gambling studies can be understood as a microcosm of the academic gaze on Indigenous peoples as described by Hokowhitu (2020) and Moreton-Robinson (2016).…”
Section: The Problem Of Representation In Indigenous Gambling Researchmentioning
confidence: 99%
“…Additionally, newer BNPL products may trigger impulsive consumer behaviours by reducing the time between purchase and consumption through mobile apps; Hundtofte and Gladstone (2017) found that mobile users are more likely to use payday loan products and engage in impulsive behaviours. Accordingly, safeguarding methods used within the gambling domain (Hilbrecht et al, 2020) could also be used to address financial vulnerability more generally. Some passive interventions and principles the personal credit industry may consider following from other domains include conveying information transparently, and helping financially educate consumers to ensure they are fully aware of the products and services they are signing up for.…”
Section: Harmful Gambling and Financial Vulnerabilitymentioning
confidence: 99%